Pengaruh Kepercayaan Merek Dan Promosi Penjualan Terhadap Minat Beli Online Di E-Commerce Shopee - Larasati, Dhiya Riska; Fadillah, Adil (LPPM IBI Kesatuan, 2022)
In this era, marketing 4.0 was introduced. Marketing that combines conventional and modern types. Marketing 4.0 can be understood like that. In the era of the digital economy, digital interactions are not enough. In fact, it is precisely at a time when the online world is growing that offline touch has become a strong point of differentiation. The purpose of this study is to analyze the Influence of Brand trust and Sales Promotion On Online Buying Interests In E-Commerce Shopee Shopee Case Study in Bogor City. The purpose of this study is (1) To find out the influence of brand trust on buying interests, (2) To know the influence of sales promotions on buying interests, (3) To know the influence of brand trust and sales promotions together affect buying interests. The number of respondents was 120 respondents taken who used Shopee. Processed with SPSS version 25, the results of the study are (1) Brand trust has a partially significant positive influence of 5,187 and greater than t-table ( df=n-k-1 or df=120-3-1=116; α=5%) = 1.65, thus H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between Brand trust (X1) on Buying Interest (Y), (2) Sales Promotion has a positive and significant influence in total of 5 ... The purpose of this study is to analyze the Influence of Brand trust and Sales Promotion On Online Buying Interests In E-Commerce Shopee Shopee Case Study in Bogor City. The purpose of this study is (1) To find out the influence of brand trust on buying interests, (2) To know the influence of sales promotions on buying interests, (3) To know the influence of brand trust and sales promotions together affect buying interests. The number of respondents was 120 respondents taken who used Shopee. Processed with SPSS version 25, the results of the study are (1) Brand trust has a partially significant positive influence of 5,187 and greater than t-table ( df=n-k-1 or df=120-3-1=116; α=5%) = 1.65, thus H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between Brand trust (X1) on Buying Interest (Y), (2) Sales Promotion has a positive and significant influence in total of 50,8%. Keywords: Brand trust, Sales Promotion, and Buying Interest.